Impact of Sonic Hedgehog‐dependent sphenoid bone defect on craniofacial growth - Hélène Guyodo; Aurélie Rizzo; Farah Diab; Fanny Noury; Svetlana Mironov; Marie deTayrac; Véronique David; Sylvie Odent; Christèle Dubourg; Valérie Dupé (Clinical and Experimental Dental Research, 2024)
Abstract Objectives The main objective of this study was to evaluate how an apparently minor anomaly of the sphenoid bone, observed in a haploinsufficient mouse model for Sonic Hedgehog (Shh), affects the growth of the adult craniofacial region. This study aims to provide valuable information to orthodontists when making decisions regarding individuals carrying SHH mutation. Materials and Methods The skulls of embryonic, juvenile and adult mice of two genotypes (Shh heterozygous and wild type) were examined and measured using landmark‐based linear dimensions. Additionally, we analysed the clinical characteristics of a group of patients and their relatives with SHH gene mutations. Results In the viable Shh+/− mouse model, bred on a C57BL/6J background, we noted the presence of a persistent foramen at the midline of the basisphenoid bone. This particular anomaly was attributed to the existence of an ectopic pituitary gland. We discovered that this anomaly led to premature closure of the intrasphenoidal synchondrosis and contributed to craniofacial deformities in adult mice, including a longitudinally shortened skull base. This developmental anomaly is reminiscent of that commonly observed in human holoprosencephaly, a disorder resulting from a deficiency in SHH activity. However, sphenoid morphogenesis is not currently monitored in individuals carrying SHH mutations. Conclusion Haploinsufficiency of Shh leads to isolated craniofacial skeletal hypoplasia in adult mouse. This finding highlights the importance of radiographic monitoring of the skull base in all individuals with SHH gene mutations.